Performance of Chimeric Trypanosoma cruzi Antigens in Serological Screening for Chagas Disease in Blood Banks - Santos, Emily Ferreira dos; Silva, Ângelo Antônio Oliveira; Freitas, Natália Erdens Maron; Leony, Leonardo Maia; Daltro, Ramona Tavares; Santos, Carlos Antônio de Souza Teles; Almeida, Maria da Conceição Chagas de; Araújo, Fernando Luiz Vieira de; Celedon, Paola Alejandra Fiorani; Krieger, Marco Aurélio; Zanchin, Nilson Ivo Tonin; Reis, Mitermayer Galvão dos; et al. (Frontiers in Medicine, 2022)
Chagas disease (CD) is among the top ten causes of inability to blood donation. Blood donation centers screen for anti-Trypanosoma cruzi antibodies using highly sensitive immunoenzymatic (ELISA) or chemiluminescent methods, which can lead to false positive results. Since positive samples cannot be used, to avoid the loss of valuable blood donations, it is necessary to improve specificity without reducing the sensitivity of the tests used for blood screening. For this purpose, our group has developed four chimeric proteins (IBMP-8.1, IBMP-8.2, IBMP-8.3, and IBMP-8.4) that have been evaluated in phase I and II studies with high performance and low cross-reactivity rates. The study included a panel of 5,014 serum samples collected from volunteer blood donors at the Hematology and Hemotherapy Foundation of the State of Bahia (Brazil). They were subjected to the detection of anti-T. cruzi antibodies, using all four IBMP antigens individually and latent class analysis (LCA) as a reference test, since there is no gold standard test for this purpose. Considering the sample size analyzed, LCA classified 4,993 (99.6%) samples as T. cruzi-negative and 21 (0.42%) as T. cruzi-positive. Sensitivity values ranged from 85.71% for IBMP-8.1 and 90.48% for IBMP-8.2 to 95.24% for IBMP-8.3 and 100% for IBMP-8.4, while specificity ranged from 99.98% for IBMP-8.3 and IBMP-8.4 to 100% for IBMP-8.1 and IBMP-8.2. Accuracy values ranged from 99.4% to 99.98%. The pretest probability for the molecules was 0.42, whereas the positive posttest probability ranged from 95.24% to 99.95% and the negative posttest probability ranged from 0.00001% to 0.0006% for all antigens. The higher odds ratio diagnosis was found for IBMP-8.4, which has been shown to be a safe single antigen for serological screening of CD in blood samples. The use of chimeric IBMP antigens is an alternative to reduce the number of bags discarded due to false-positive results. These molecules have high diagnostic performance and were shown to be suitable for use in screening CD in blood banks, isolated (IBMP-8.4) or in combination; and their use in blood banks could significantly reduce unnecessary disposal of blood bags or the risk of T. cruzi transmission.